Design and development of integrated transplanter and weedermmachine for system of rice intesification (SRI) cultivation in Malaysia / Mohd Syedi Imran Bin Mohd Dawi. - Mohd Syedi Imran Mohd Dawi (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2015)
The objectives for this research are to design and develop an integrated chassis in order to attach rice transplanter and weeding mechanism for System of Rice Intensification (SRI); to design and analyze a seedling rice transplanter mechanism; to design and develop a weeding mechanism which is able to cover three rows between crops at one time; and to analyze and evaluate the performance of prototype machine.